(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The corpus, being an effective tool, is utilized in multiple fields. One of them is the Translation. However, this resource isn´t used frequently in translation studies when one of the languages in question is classical chinese (written language used anciently in China). And when it comes to an ad hoc parallel corpus, the steps of how to create it are usually omitted by researchers who make such investigations. The objective of this article is to present how to elaborate a classic Chinese-Spanish parallel corpus taking as example the historic novel Romance of the Three Kingdoms and its two translations into Spanish. To reach the objective, we have described the problem of creation and exploitation of this type of corpus, following the order of the phases of the process. We’ve found that some of the phases are universal while other phases are unique for old languages and for the linguistic combination Chinese-other language. And in this latter case, there’s a lack of effective applications. With the current work, we hope to offer useful information to those scholars who are willing to carry out their own investigations based on self-built parallel corpus and at the same time related to the classic Chinese works.